Sub-10 nm surface-aminated silica, and preparation method and application thereof

CN122772267APending Publication Date: 2026-09-18NINGBO NEPTUNIUM NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610820404.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-08
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

为此,本发明的实施例提出一种亚十纳米表面氨基化二氧化硅的制备方法,将制得的亚十纳米表面氨基化二氧化硅用于TPU中制备复合材料,解决现有技术中TPU无法兼顾强度和断裂伸长率,且无法满足高频形变场景需求的问题

Benefits of technology

(1)采用亚十纳米表面氨基化二氧化硅的尺寸为1~5nm,该尺寸与TPU硬段微区(5~10nm)匹配,可以嵌入硬-软段界面,消除界面空隙,避免应力集中;且纳米二氧化硅作为异质形核点诱导TPU硬段结晶,形成“纳米点-硬段”协同网络,增强硬段锚固作用,限制软段过度滑移,弹性回复率从95%提升至98%;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122772267A_ABST
    Figure CN122772267A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of composite materials, in particular to sub-10-nanometer surface aminosilica and a preparation method and application thereof. The preparation method of the sub-10-nanometer surface aminosilica provided by the application comprises the following steps: (1) preparing a mixed solvent by mixing double-distilled water, isopropyl alcohol and acetone, and adjusting the pH value to be alkaline; (2) adding organic aminosilane and ammonia water into the mixed solvent obtained in the step (1) to form a mixed solution, and performing centrifugal washing after reaction. The sub-10-nanometer surface aminosilica prepared by the preparation method has a particle size of 1-5 nm, and the surface is modified by aminosilane; the aminosilica is used for preparing a composite material, the aminosilica and a matrix have good interface bonding force, the composite material has excellent fatigue life and elastic recovery rate, and can meet the use requirements in different fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material technology, specifically relating to a sub-10 nanometer surface-aminated silica, its preparation method, and its application. Background Technology

[0002] Thermoplastic polyurethane elastomer (TPU) is a versatile polymer material widely used in footwear, cables, clothing, automobiles, pharmaceuticals, pipes, films, and sheets. TPU is a block linear polymer composed of flexible soft segments and rigid hard segments. The content of the hard segments directly affects hydrogen bonding, microphase separation, and crystallinity, making it a major factor determining TPU performance. Generally, as the hard segment content increases, the hardness, modulus, and tear strength of TPU increase, while the elongation at break decreases. Furthermore, the molecular weight of TPU also significantly affects its mechanical properties; as the molecular weight increases, tensile strength, modulus, and abrasion resistance improve significantly. However, currently produced TPUs are prone to debonding at the interface between the soft and hard segments under dynamic cyclic loading, resulting in a fatigue life of only 10... 4 ~10 5 The cycle test (GB / T 14467-2006 standard test) cannot meet the requirements of high-frequency deformation scenarios.

[0003] Adding inorganic nanomaterials is a common technique for TPU modification, typically involving the addition of nano-silica, nano-calcium carbonate, and nano-zinc oxide to improve various TPU properties. However, the nanomaterials used in these techniques are larger than 10 nm, making them prone to agglomeration in the TPU matrix, forming stress concentration points and resulting in a 10-20% reduction in fatigue life. While adding graphene / carbon nanotubes can improve the strength of the composite material, their large aspect ratio (>50) makes dispersion difficult, leading to easy breakage during processing and fatigue performance fluctuations of up to ±20%. To better disperse nanomaterials in the TPU matrix, hydroxylation or carboxylation modifications are performed on their surfaces. However, this only results in a single physical entanglement with the TPU matrix, with an interfacial bonding strength ≤15 MPa, which is insufficient for effective load transfer.

[0004] Therefore, how to modify TPU to meet the application requirements of high-frequency forming scenarios has received increasing attention from technical personnel. Summary of the Invention

[0005] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, embodiments of this invention propose a method for preparing sub-10 nanometer surface-aminated silica, which is then used in TPU to prepare composite materials. This addresses the problem in existing technologies where TPU cannot simultaneously achieve both strength and elongation at break, and cannot meet the requirements of high-frequency deformation scenarios.

[0006] The objective of this invention is mainly achieved through the following technical solutions: On one hand, the present invention provides a method for preparing sub-10 nanometer surface-aminated silica, comprising the following steps: (1) A mixed solvent was prepared by mixing double-distilled water, isopropanol and acetone, and the pH was adjusted to be alkaline; (2) Add organic aminosilane and ammonia to the mixed solvent obtained in step (1) to form a mixed solution, and then centrifuge and wash after the reaction.

[0007] In this invention, a mixed solvent is prepared by mixing double-distilled water, isopropanol, and acetone. The impurity content in the double-distilled water is extremely low, thus avoiding the impact of impurities on the quality of the silica product. Isopropanol and acetone are beneficial for the dispersion of raw materials and silica particles, reducing surface tension and agglomeration. The mixed solvent system of the two can exert a synergistic effect, resulting in more beneficial effects.

[0008] During the reaction, the organoaminosilane first undergoes hydrolysis to generate nascent particles. The hydroxyl groups between these nascent ions undergo dehydration condensation, gradually increasing in size. Then, under the influence of the mixed solvent, the contact between large-scale particles is low, while the contact between large-scale particles and nascent particles is high. Therefore, the growth is slow, controllable, and less prone to aggregation. Controlling the reaction conditions allows for the preparation of extremely small particles, sub-ten nanometers in size, with a narrow particle size distribution.

[0009] Optionally, in step (1), the volume ratio of the double-distilled water, isopropanol, and acetone is 6:(2~3):(1~2). And / or, in step (1), ammonia is used to adjust the pH to 7.5~8.5.

[0010] Optionally, in step (2), the organic amino silane includes at least one of 3-aminopropyltrimethoxysilane or 3-aminopropyltriethoxysilane; And / or, in step (2), the concentration of the organic aminosilane in the mixed solution is 0.05~2 mol / L, and the total concentration of ammonia is 0.01~0.1 mol / L; Drink / or, in step (2), the reaction temperature is 45~60℃, the reaction time is 1~3h, and the evaporated gas is condensed and recovered during the reaction; And / or, in step (2), the centrifugal washing is performed using ethanol, the centrifugal washing speed is 15000~20000 rpm, and the centrifugal washing is performed at least 3 times.

[0011] The present invention also provides a sub-10 nanometer surface-aminated silica, which is prepared by the above-described preparation method.

[0012] Optionally, the sub-10 nanometer surface aminated silica has an amino grafting rate of greater than 80% and a particle size of 1~5 nm.

[0013] On the other hand, the present invention provides a TPU fatigue-resistant composite material, comprising a thermoplastic polyurethane elastomer and sub-10 nanometer surface aminated silica prepared by the above preparation method or the above-mentioned sub-10 nanometer surface aminated silica.

[0014] Optionally, the amount of sub-10 nm surface-aminated silica added to the composite material is 1~5 wt%.

[0015] The present invention also provides a method for preparing TPU fatigue-resistant composite material, comprising the following steps: dispersing the sub-10 nanometer surface aminated silica in an organic solvent and then blending it with TPU granules, followed by extrusion granulation or injection molding to obtain a sample.

[0016] Optionally, in step (2), the mass ratio of the sub-10 nanometer surface-aminated silica to the organic solvent is 30-60%; the organic solvent includes at least one of ethylene glycol, glycerol, or N,N-dimethylformamide. And / or, in step (2), the dispersion treatment is ultrasonic dispersion or ball milling dispersion, the ultrasonic dispersion power is 100~300 W, the ultrasonic dispersion time is 10~20 min; the ball milling dispersion speed is 200~400 rpm, the ball milling dispersion time is 20~40 min; And / or, in step (2), the blending process is carried out using a twin-screw extruder or a mixer. The twin-screw extruder has a rotation speed of 500~700 rpm, a zone temperature of 130~150℃, a zone temperature of 140~155℃, and a zone temperature of 150~160℃. The mixer has a temperature of 100~120℃ and a mixing time of 5~15 min.

[0017] Optionally, in step (2), the length of the extruded granules is 2~5mm, and the cooling water temperature is 5~15℃; And / or, in step (2), the temperature of the injection molding mold is 50~70℃ and the injection pressure is 60~100MPa.

[0018] The technical advantages of the method for preparing the TPU fatigue-resistant composite material of the present invention are as follows: (1) The size of the sub-10 nm surface-aminated silica is 1~5 nm, which matches the TPU hard segment micro-region (5~10 nm). It can be embedded in the hard-soft segment interface, eliminate interface voids, and avoid stress concentration. Moreover, the nano silica acts as a heterogeneous nucleation point to induce TPU hard segment crystallization, forming a "nano point-hard segment" synergistic network, which enhances the hard segment anchoring effect, limits the excessive slippage of the soft segment, and increases the elastic recovery rate from 95% to 98%. (2) The high-density amino groups form “hydrogen bonds (bond energy 25~30kJ / mol) + dynamic urea bonds (reversible covalent bonds)” with the urethane groups in TPU, which increases the interfacial bonding force between the nanomaterial and the matrix to 30MPa or more. (3) Nanofluid pre-dispersion ensures dispersion >95% (SEM observation shows agglomeration rate <3%), and twin-screw temperature gradient prevents TPU degradation (yellowing index ≤1.0). Attached Figure Description

[0019] Figure 1 These are particle size diagrams of the silica prepared in Examples 1-2 and Comparative Examples 1-2; Figure 2 This is a transmission electron microscope (TEM) image of the silica prepared in Example 1; Figure 3 This is a stress-tensile curve of the series of composite materials obtained in Example 3; Figure 4 This is a stress-tensile curve of the series of composite materials prepared in Comparative Example 3; Figure 5 This is a repeated tensile stress-deformation curve of the composite material with a silica addition of 6wt% prepared in Example 3. Figure 6 This is a repeated tensile stress-deformation curve of the composite material with a silica content of 6 wt% prepared in Comparative Example 3. Detailed Implementation

[0020] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0021] On one hand, the present invention provides a method for preparing sub-10 nanometer surface-aminated silica, comprising the following steps: (1) A mixed solvent was prepared by mixing double-distilled water, isopropanol and acetone, and the pH was adjusted to be alkaline; (2) Add organic aminosilane and ammonia to the mixed solvent obtained in step (1) to form a mixed solution, and then centrifuge and wash after the reaction.

[0022] Optionally, in step (1), the volume ratio of the double-distilled water, isopropanol, and acetone is 6:(2~3):(1~2); for example, 6:3:1 or 6:2:2, etc. And / or, in step (1), ammonia is used to adjust the pH to 7.5-8.5. The pH of the environment has a significant impact on the reaction rate; both acidic and alkaline conditions can catalyze and accelerate the hydrolysis reaction, especially the presence of hydroxide ions (OH-) in an alkaline environment. - The reaction is more effective due to its strong nucleophilicity. Researchers found that at a weakly alkaline pH, the hydrolysis process is moderately rapid and highly controllable, producing particles that are sub-ten nanometers in size and have a narrow distribution. Conversely, higher pH and acidic environments produce particles that are larger in size and have a wider distribution.

[0023] Optionally, in step (2), the organic amino silane includes at least one of 3-aminopropyltrimethoxysilane or 3-aminopropyltriethoxysilane; And / or, in step (2), the concentration of the organic aminosilane in the mixed solution is 0.05~2 mol / L, for example 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, or 2 mol / L, etc., and the total ammonia concentration is 0.01~0.1 mol / L, for example 0.01 mol / L, 0.02 mol / L, 0.04 mol / L, 0.06 mol / L, 0.08 mol / L, or 0.1 mol / L, etc. Limiting the concentration of the organic aminosilane and the total ammonia concentration ensures that the prepared silica has a high amino grafting rate.

[0024] And / or, in step (2), the reaction temperature is 45~60℃, the reaction time is 1~3h, and the evaporated gas is condensed and recovered during the reaction. Controlling the reaction temperature within the above range can not only increase the reaction rate, but also avoid the problem of particle agglomeration caused by excessively high temperature and violent reaction. In addition, since acetone in the mixed solvent is very volatile, condensation and recovery can reduce acetone consumption and reduce production costs.

[0025] Optionally, in step (2), the centrifugal washing is performed using ethanol, the centrifugal washing speed is 15000~20000 rpm, and the centrifugal washing is performed at least 3 times.

[0026] The present invention also provides a sub-10 nanometer surface-aminated silica, which is prepared by the above-described preparation method.

[0027] Optionally, the amino grafting rate of the sub-10 nanometer surface aminated silica is greater than 80%, preferably greater than 85%, more preferably greater than 90%, and most preferably greater than 95%, and the particle size of the sub-10 nanometer surface aminated silica is 1~5 nm, preferably 2~4 nm.

[0028] In this embodiment of the invention, the particle size is limited to 1~5 nm, which matches the TPU hard segment micro-region (5~10 nm). This size can be embedded into the hard-soft segment interface, eliminating interface voids, avoiding stress concentration, and forming a "nanodot-hard segment" synergistic network. This enhances the hard segment anchoring effect, limits excessive soft segment slippage, and increases the elastic recovery rate from 95% to 98%. If the particle size is too small, it is easier to aggregate; if the particle size is too large, it will lead to a certain degree of hard segment micro-region aggregation, which has an adverse effect on the formation of the synergistic network.

[0029] On the other hand, the present invention provides a TPU fatigue-resistant composite material, comprising a thermoplastic polyurethane elastomer and sub-10 nanometer surface aminated silica prepared by the above preparation method or the above-mentioned sub-10 nanometer surface aminated silica.

[0030] In this embodiment of the invention, TPU fatigue-resistant composite material is prepared by using sub-10 nanometer surface aminated silica. The amino groups form hydrogen bonds and dynamic urea bonds (dynamic covalent bonds) with the urethane groups in TPU, thereby increasing the interfacial bonding force between silica and the matrix to 35 MPa.

[0031] Optionally, the amount of sub-10 nm surface-aminated silica added to the composite material is 1~5 wt.%, for example, 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.% or 5 wt.%.

[0032] In this embodiment of the invention, limiting the amount of sub-10 nm surface-aminated silica added to the composite material can improve the fatigue resistance and bending resistance of the composite material; if the amount of sub-10 nm surface-aminated silica added to the composite material is too low or too high, the fatigue resistance and bending resistance of the composite material will not reach the ideal state.

[0033] The present invention also provides a method for preparing TPU fatigue-resistant composite material, comprising the following steps: dispersing the sub-10 nanometer surface aminated silica in an organic solvent and then blending it with TPU granules, followed by extrusion granulation or injection molding to obtain a sample.

[0034] Optionally, in step (2), the mass ratio of the sub-10 nanometer surface-aminated silica to the organic solvent is 30-60%; the organic solvent includes at least one of ethylene glycol, glycerol, or N,N-dimethylformamide.

[0035] Optionally, in step (2), the dispersion treatment is ultrasonic dispersion or ball milling dispersion. The power of ultrasonic dispersion is 100~300 W, such as 100W, 150W, 200W, 250W or 300W, and the ultrasonic dispersion time is 10~20 min, such as 10min, 12min, 14min, 16min, 18min or 20min, etc. The rotation speed of ball milling dispersion is 200~400 rpm, such as 200rpm, 250rpm, 300rpm, 350rpm or 400rpm, etc., and the ball milling dispersion time is 20~40 min, such as 20min, 25min, 30min, 35min or 40min, etc.

[0036] Optionally, in step (2), the blending process is carried out using a twin-screw extruder or a mixer. The twin-screw extruder has a rotation speed of 500~700 rpm, a zone temperature of 130~150℃, a zone temperature of 140~155℃, and a zone temperature of 150~160℃. The mixer has a temperature of 100~120℃ and a mixing time of 5~15 min.

[0037] Optionally, in step (2), the length of the extruded granules is 2~5mm, and the cooling water temperature is 5~15℃; And / or, in step (2), the temperature of the injection molding mold is 50~70℃ and the injection pressure is 60~100MPa.

[0038] The present invention also provides the application of the above-mentioned TPU fatigue-resistant composite material or the TPU fatigue-resistant composite material prepared by the above-mentioned preparation method in the fields of flexible electronics, medical and health, automotive industry or sporting goods.

[0039] The technical advantages of the method for preparing the TPU fatigue-resistant composite material of the present invention are as follows: (1) The size of the sub-10 nm surface aminated silica is 1~5 nm, which matches the TPU hard segment micro-region (5~10 nm). It can be embedded in the hard-soft segment interface, eliminate interface voids, and avoid stress concentration. Moreover, the nanodots act as heterogeneous nucleation points, inducing TPU hard segment crystallization and forming a “nanodot-hard segment” synergistic network, which enhances the hard segment anchoring effect, limits the excessive slippage of the soft segment, and increases the elastic recovery rate from 95% to 98%. (2) The high-density amino groups form “hydrogen bonds (bond energy 25~30kJ / mol) + dynamic urea bonds (reversible covalent bonds)” with the urethane groups in TPU, which increases the interfacial bonding force between the nanomaterial and the matrix to 30MPa or more. (3) Nanofluid pre-dispersion ensures dispersion >95% (SEM observation shows agglomeration rate <3%), and twin-screw temperature gradient prevents TPU degradation (yellowing index ≤1.0).

[0040] The technical solution of the present invention will now be described in detail with reference to specific embodiments and accompanying drawings.

[0041] Example 1 (1) Prepare a mixed solvent by mixing 0.6 mL of double-distilled water, 0.2 mL of isopropanol and 0.2 mL of acetone, and adjust the pH value to 8 by using ammonia water; (2) 3-aminopropyltrimethoxysilane and ammonia water are added to the mixed solvent obtained in step (1) to form a mixed solution. The concentration of 3-aminopropyltrimethoxysilane in the mixed solution is 1 mol / L and the total concentration of ammonia is 0.05 mol / L. The reaction is carried out at 50°C for 3 h. During the reaction, condensation and recovery are performed. The solution is washed three times by centrifugation with ethanol. The amino grafting rate of the sub-10 nanometer surface amino-modified silica is 95%.

[0042] Example 2 The preparation method of this embodiment is the same as that of Example 1, except that in step (1), 0.6 mL of double-distilled water, 0.3 mL of isopropanol and 0.1 mL of acetone are mixed to prepare a mixed solvent; the amino grafting rate of the sub-10 nanometer surface aminated silica is 92%.

[0043] Comparative Example 1 The preparation method of this embodiment is the same as that of Example 1, except that: in step (1), 1 mL of double-distilled water is used as the solvent; the amino grafting rate of the sub-10 nanometer surface aminated silica is 91%.

[0044] Comparative Example 2 The preparation method of this embodiment is the same as that of Example 1, except that in step (1), 0.6 mL of double-distilled water and 0.4 mL of isoacetone are used to prepare a mixed solvent; the amino grafting rate of the sub-10 nanometer surface aminated silica is 93%.

[0045] The materials prepared in Examples 1-2 and Comparative Examples 1-2 were characterized, and the results are as follows: Figure 1 As shown. From Figure 1 As can be seen, the addition of isopropanol reduces the size and narrows the size distribution of the ultrafine silicon dots; the addition of acetone results in even finer size and more uniform distribution, reaching sub-ten nanometers. Furthermore, the smallest size and narrowest distribution are achieved when the acetone content is increased to 20%. The transmission electron microscope image of the nano-silica prepared in Example 1 is shown below. Figure 2 As shown, from Figure 2As can be seen, the nano-silica prepared in Example 1 has a particle size of 1~5nm and the nanoparticles are uniformly dispersed.

[0046] Example 3 The sub-10-nanometer surface-aminated silica prepared in Example 1 was dispersed in ethylene glycol, wherein the mass ratio of sub-10-nanometer surface-aminated silica to ethylene glycol was 50%. After ultrasonic dispersion at 200W for 15 min, it was mixed with TPU granules in a mixer at 110°C for 10 min, and then injection molded at 60°C and 90MPa. The amount of sub-10-nanometer surface-aminated silica added in the composite material was 2wt%, 4wt%, 6wt%, and 8wt%, respectively.

[0047] Comparative Example 3 (1) Prepare a mixed solvent by mixing 0.6 mL of double-distilled water, 0.2 mL of isopropanol and 0.2 mL of acetone, and adjust the pH value to 8 by using ammonia water; (2) Add 3-trimethoxysilane to the mixed solvent obtained in step (1) to form a mixed solution, wherein the concentration of 3-trimethoxysilane in the mixed solution is 1 mol / L, and the reaction is carried out at 50°C for 3 h, and the solution is washed three times by centrifugation with ethanol. (3) The prepared sub-10 nanometer surface hydroxylated silica was dispersed in ethylene glycol, wherein the mass ratio of sub-10 nanometer surface hydroxylated silica to ethylene glycol was 50%. After ultrasonic dispersion at 200W for 15min, it was mixed with TPU granules in a mixer at 110℃ for 10min, and then injection molded at 60℃ and 90MPa. The amount of sub-10 nanometer surface hydroxylated silica added in the composite material was 2wt%, 4wt%, 6wt%, and 8wt%, respectively.

[0048] Tensile tests were performed on the series of composite materials prepared in Example 3 and Comparative Example 3. The stress-tensile curve of Example 3 is shown below. Figure 3 As shown, the stress-tension curve of Comparative Example 3 is as follows: Figure 4 As shown. From Figure 3 and Figure 4 As can be seen, with the addition of sub-10 nm surface-hydroxylated silica, the strength of the TPU composite resin increases while the elongation at break decreases. The composite material prepared by adding sub-10 nm surface-aminated silica shows a significant increase in strength without a substantial loss in elongation at break, indicating that surface-aminated silica modification has a very beneficial effect on maintaining both strength and toughness.

[0049] Repeated tensile tests were performed on the composite materials with a silica content of 6 wt% prepared in Example 3 and Comparative Example 3. The stress-tensile curve of the composite material with a silica content of 6 wt% prepared in Example 3 is shown below. Figure 5 As shown, the stress-tensile curve of the composite material with a silica addition of 6 wt% prepared in Comparative Example 3 is as follows. Figure 6 As shown. From Figure 5 and Figure 6 As can be seen, the strength of the TPU composite resin with surface hydroxyl ultrafine silica dots decreases with increasing number of tensile cycles. When the number of tensile cycles reaches hundreds of thousands or millions, the tensile curve deviates significantly from the initial condition. In contrast, surface amino ultrafine silica dots maintain excellent repeatability even at millions of tensile cycles. Therefore, they significantly improve the material's bending resistance and aging resistance.

[0050] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0051] Although the above embodiments have been shown and described, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions and variations made to the above embodiments by those skilled in the art are within the protection scope of the present invention.

Claims

1. A method for preparing sub-10 nanometer surface-treated aminated silica, characterized in that, Includes the following steps: (1) A mixed solvent was prepared by mixing double-distilled water, isopropanol and acetone, and the pH was adjusted to be alkaline; (2) Add organic aminosilane and ammonia to the mixed solvent obtained in step (1) to form a mixed solution, and then centrifuge and wash after the reaction.

2. The method for preparing sub-10 nanometer surface-aminated silica according to claim 1, characterized in that, In step (1), the volume ratio of the double-distilled water, isopropanol and acetone is 6:(2~3):(1~2). And / or, in step (1), ammonia is used to adjust the pH to 7.5~8.

5.

3. The method for preparing sub-10 nanometer surface-aminated silica according to claim 1, characterized in that, In step (2), the organic amino silane includes at least one of 3-aminopropyltrimethoxysilane or 3-aminopropyltriethoxysilane; And / or, in step (2), the concentration of the organic aminosilane in the mixed solution is 0.05~2 mol / L, and the total concentration of ammonia is 0.01~0.1 mol / L; And / or, in step (2), the reaction temperature is 45~60℃, the reaction time is 1~3h, and the evaporated gas is condensed and recovered during the reaction; And / or, in step (2), the centrifugal washing is performed using ethanol, the centrifugal washing speed is 15000~20000 rpm, and the centrifugal washing is performed at least 3 times.

4. A sub-10 nanometer surface-aminated silica, characterized in that, It is prepared by any one of claims 1 to 3.

5. The sub-10 nanometer surface-aminated silica according to claim 5, characterized in that, The sub-10 nm surface-aminated silica has an amino grafting rate of greater than 80% and a particle size of 1~5 nm.

6. A TPU fatigue-resistant composite material, characterized in that, The raw materials include thermoplastic polyurethane elastomer and sub-10 nanometer surface-aminated silica prepared by any one of claims 1 to 3, or sub-10 nanometer surface-aminated silica as described in claims 4 or 5.

7. The TPU fatigue-resistant composite material according to claim 6, characterized in that, The amount of sub-10 nanometer surface-aminated silica added in the composite material is 1~5 wt.%.

8. The method for preparing the TPU fatigue-resistant composite material according to claim 6 or 7, characterized in that, Includes the following steps: The sub-10 nanometer surface-aminated silica is dispersed in an organic solvent and then blended with TPU granules, followed by extrusion granulation or injection molding to obtain a sample.

9. The method for preparing the TPU fatigue-resistant composite material according to claim 8, characterized in that, The mass ratio of the sub-10 nanometer surface-aminated silica to the organic solvent is 30-60%; the organic solvent includes at least one of ethylene glycol, glycerol, or N,N-dimethylformamide. And / or, the dispersion treatment is ultrasonic dispersion or ball milling dispersion, wherein the ultrasonic dispersion power is 100~300 W and the ultrasonic dispersion time is 10~20 min; the ball milling dispersion rotation speed is 200~400 rpm and the ball milling dispersion time is 20~40 min; And / or, the blending process is carried out using a twin-screw extruder or a mixer, wherein the twin-screw extruder has a rotation speed of 500~700 rpm, a zone 1 temperature of 130~150℃, a zone 2 temperature of 140~155℃, and a zone 3 temperature of 150~160℃; and the mixer has a temperature of 100~120℃ and a mixing time of 5~15 min.

10. The method for preparing the composite material according to claim 8, characterized in that, The extrusion granulation produces granules with a length of 2-5 mm and a cooling water temperature of 5-15 ℃. And / or, the temperature of the injection molding mold is 50~70 ℃, and the injection pressure is 60~100 MPa.